2019
DOI: 10.1126/scitranslmed.aav6278
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted hippocampal growth hormone secretagogue receptor 1α interaction with dopamine receptor D1 plays a role in Alzheimer′s disease

Abstract: Hippocampal lesions are a defining pathology of Alzheimer’s disease (AD). However, the molecular mechanisms that underlie hippocampal synaptic injury in AD have not been fully elucidated. Current therapeutic efforts for AD treatment are not effective in correcting hippocampal synaptic deficits. Growth hormone secretagogue receptor 1α (GHSR1α) is critical for hippocampal synaptic physiology. Here, we report that GHSR1α interaction with β-amyloid (Aβ) suppresses GHSR1α activation, leading to compromised GHSR1α r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 76 publications
2
50
0
Order By: Relevance
“…Most importantly, it is been proven that Aβ combines with GHSR1α, preventing activation of GHSR1α and GHSR1α/DRD1 heterodimerization. The resultant reduced GHSR1α/DRD1 interaction contributes to hippocampal synaptic injury, leading to memory damage (101).…”
Section: Aβ Interact With Hippocampal Ghrelin/ghsr1α Signaling In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, it is been proven that Aβ combines with GHSR1α, preventing activation of GHSR1α and GHSR1α/DRD1 heterodimerization. The resultant reduced GHSR1α/DRD1 interaction contributes to hippocampal synaptic injury, leading to memory damage (101).…”
Section: Aβ Interact With Hippocampal Ghrelin/ghsr1α Signaling In Admentioning
confidence: 99%
“…These results may reflect the insensitivity of GHSR1α to activators in AD patients. Furthermore, it has been shown that the combined activation of GHSR1α and DRD1 with their selective agonists MK0677 and SKF81297, respectively, rescues hippocampal synaptic function and cognition from Aβ toxicity in young 5XFAD mice (101). However, whether MK0677/SKF81297 is beneficial for older 5XFAD mice requires further investigation.…”
Section: Aβ Interact With Hippocampal Ghrelin/ghsr1α Signaling In Admentioning
confidence: 99%
“…This observation, together with the ineffectiveness of MK0677 as seen in our study and a previous clinical trial [19], seems to suggest a suppressed GHSR1α response to its ligand-or agonist-induced activation in AD-relevant pathophysiological settings. Indeed, we have determined that complexation with Aβ inhibits ligand-induced activation of GHSR1α and thus suppresses GHSR1α's regulation of dopamine receptor D1 (DRD1), leading to hippocampal synaptic deficits [60]. We therefore form a "ghrelin resistance" hypothesis of AD hippocampal synaptic failure.…”
Section: Discussionmentioning
confidence: 98%
“…As previously mentioned, AKAP5 is a gene related to synaptic plasticity and memory and is part of a LncACeNET in AD [ 96 ]. As for DRD1, it is a dopamine receptor whose dysregulation could contribute to synaptic injury in AD [ 158 ].…”
Section: Cerna Network and Neurodegenerative Diseasesmentioning
confidence: 99%